Nitrogen supplementation with sago 'hampas' hydrolysate for low cost bioethanol fermentation media - Jomoi, Alfrida (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Nitrogen source is very important in the production of the bioethanol. Starchy materials such as sago 'hampas' which can be found abundantly in Malaysia is one of the suitable sources for the production of bioethanol. The main focus of this study is to find out which type of nitrogen sources is the best for the fennentation of bioethanol. Previous studies showed that the best nitrogen source is the yeast extract. However, yeast extracts are expensive and this research also focus on to find which nitrogen sources are cheaper to replace yeast extract and also may decrease the production cost. Four types of nitrogen sources were used namely peptone, ammonium sulphate, yeast extract and urea. The effect of these different sources of nitrogen in the production ofbioethanol were evaluated in this study. Sago 'hampas' was treated with the Liquozyme and Spirizyme for the saccharification of starch and undergo three cycles of enzymatic hydrolysis in order to get sago 'hampas' hydrolysate (SHH). Two replicates were prepared for each type of nitrogen sources. The SHH were fermented by yeast or Saccharomyces cerevisiae in 250 mL of Erlenmeyer flask with 100 mL of media and batch fermentation will be used in this study. From this study SHH were able to provide glucose needed during fermentation in the production of bioethanol. Urea, peptone and ammonium sulfate can replaced the yeast extract as the sources ofnitrogen in fermentation.